The Fear of COVID-19 Infection one Year After Business Reopening in Iranian Society - Mohsen Poursadeqiyan; Nayyereh Kasiri; Behzad Khedri; Zahra Ghalichi Zaveh; Amin Babaei Pouya; Somayeh Barzanouni; milad Abbasi; Maryam Feiz Arefi; Farahnaz Khajehnasiri; Naser Dehghan (Shiraz University of Medical Sciences, 2022)
Background: People's participation in more efficient control of the disease and public awareness about the risk of COVID-19 affect their preventive behavior. This study examines the level of fear of COVID-19 infection in Iranian society after returning to social activities and business reopening. Methods: This Cross-Sectional study consisted of urban dwellers in Iran, and the data gathering tool was a researcher-designed questionnaire. To design the instrument, the authors interviewed experts and ordinary people to determine the key questions . Then, the questions were modified and finalized based on the experts' feedback and a reexamination by the experts after two weeks. An online version of the questionnaire was disseminated using social networks. 168 people were included in the study by the available sampling method. Data were analyzed through descriptive statistics methods. Quantitative data as mean and standard deviation were reported, and the qualitative data were reported as numbers. Chi-square test and Spearman correlation coefficient were used to examine the relationship between questions related to COVID-19 infection fear and demographic variables. Data analyses were done in SPSS 20. Results: The study was carried out on 168 participants, and 78 of them were employees of different offices. The participants believed that among the ways of spreading the disease, kissing and hugging (n=142, 84.5%), shaking hands (n=127, 75.6%), contact with the saliva of an infected person (n=116, 69.0%), and spread through the air (n=60, 35.7%) had the highest frequencies. Conclusion: Fear of COVID-19 infection in the participants was at moderate and above moderate levels. The participants also hoped that the vaccine would be found and made available to the public. Policy-makers in the health sector can use the results.